2010
DOI: 10.1007/s11258-010-9746-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of urban land use on seed dispersal and wetland invasibility

Abstract: Urban habitats are generally considered highly invaded by exotic species due to the frequency and extent of disturbance caused by human activities and development. Our previous study had demonstrated that forested wetlands within residential areas are more extensively invaded than wetlands within industrial-commercial areas. In this study, we investigate whether the structure of the forest edge and seed dispersal can explain the differential in the invasion of wetlands surrounded by industrial and residential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Thus, the hypothesis of greater species richness in the rural fragment was not accepted. This behavior is opposite to that registered in the literature, where is a trend of greater species richness in rural fragments over time (Campos et al, 2009;Cutway & Ehrenfeld, 2010;Freitas et al, 2013;Knorr & Gottsberg, 2012;Overdyck & Clarkson, 2012).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Thus, the hypothesis of greater species richness in the rural fragment was not accepted. This behavior is opposite to that registered in the literature, where is a trend of greater species richness in rural fragments over time (Campos et al, 2009;Cutway & Ehrenfeld, 2010;Freitas et al, 2013;Knorr & Gottsberg, 2012;Overdyck & Clarkson, 2012).…”
Section: Discussioncontrasting
confidence: 70%
“…that in rural fragment (Cole et al, 2010;Freitas et al, 2013;Knorr & Gottsberg, 2012;Overdyck & Clarkson, 2012) the seed density was higher than recorded for urban forests (Campos et al, 2009;Cutway & Ehrenfeld, 2010;Overdyck & Clarkson, 2012;Pivello et al, 2006). When the seed density of rural and urban fragments inserted in the same landscape is compared, as in the case of this study, it is verified that the seed number remains superior in the rural fragment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Azous and Horner (2000) found high toxic metal accumulation in inlet zones of wetlands caused by urban runoff, which affected wetlands when their concentrations exceeded the absorbable limit of wetlands. Cutway and Ehrenfeld (2010) identified that wetlands within residential and industrial areas were suffering more extensive and severe biological invasions, which were threatening the ecological balance that was structured around the water environment as core. On the other hand, Ji and Murambadoro (2010) observed that new open waters such as reservoirs, ponds, and lakes were created as part of planned urban development.…”
Section: Introductionmentioning
confidence: 99%
“…Urban wetlands are highly anthropogenically influenced ecosystems in urban landscapes [7][8][9][10], which can lead to an increase in water pollutants and exotic species [11]. Larson et al [12] sampled vegetation and soils from eight urban wetlands and compared them to six forested wetlands, five shrubby wetlands, and seven newly constructed wetlands.…”
Section: Introductionmentioning
confidence: 99%